Potential Development of Islamic Fintech in Supporting the Growth of the Halal Industry - Iman Supriadi; Maghfiroh, Rahma Ulfa; Abadi, Rukhul (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Background: The halal industry and Islamic fintech are two sectors that are growing rapidly. Both have great potential to support the growth of the Islamic economy and finance. However, there is still potential that has yet to be fully utilized in the development of Islamic fintech to support the growth of the halal industry. Objectives: This paper aims to identify the potential development of Islamic fintech in supporting the growth of the halal industry and analyze the implications of such development. Novelty: This study provides a deeper understanding of the potential and implications of the development of Islamic fintech in the context of the halal industry. This study also guides industry players in utilizing Islamic fintech to support the growth of the halal industry and strengthen the literature and knowledge related to the development of Islamic fintech in the context of the halal industry. Research Methodology / Design: This study uses a qualitative research approach by conducting a literature review on the development of Islamic fintech and the halal industry. The data obtained is compiled and analyzed to identify the potential development of Islamic fintech in supporting the growth of the halal industry. Findings: This study reveals several important findings. First, government involvement in regulatory development has supported the growth of Islamic fintech in the halal industry. Second, collaboration between the technology industry and the financial sector has accelerated the progress of Islamic fintech and optimized financial accessibility in the halal industry. Third, the improvement of Islamic financial literacy and education is an important factor in increasing the adoption of Islamic fintech in the halal industry. Lastly, the utilization of appropriate technologies, such as blockchain and artificial intelligence, has boosted the growth of the halal industry through Islamic fintech. Implication: The development of Islamic fintech can make a positive contribution to the growth of the halal industry by providing financial solutions that comply with Sharia principles. This opens up opportunities to increase the competitiveness of the halal industry globally. The implications of this study can also serve as a guide for the government, technology industry, Islamic financial institutions, and halal industry players in optimizing the development of Islamic fintech and increasing financial inclusion in the halal industry.